"Salience network" dysfunction hypothesis in autism spectrum disorders. (8th April 2013) - Toyomaki, Atsuhito; Murohashi, Harumitsu
Abstract: Autism spectrum disorder (ASD) is a neurodevelopmental disorder characterized by impaired social interaction and communication, as well as repetitive and stereotyped patterns of behavior. Although most patients with ASD show sensory abnormalities such as hyperesthesia and hypoesthesia, its relation to social cognition has not been well studied. Recently, a salience network (SN) dysfunction hypothesis of ASD has been proposed. This neuroscientific hypothesis might explain how a SN integrating external sensory stimuli with internal states mediates interactions between large‐scale networks involved in externally and internally oriented cognitive processing. In the brain of patients with ASD, areas of the SN, including the anterior insula, become dysfunctional, which results in difficulty in operating social cognition and self‐referential processing. Here we discuss the controversial points and future directions of this hypothesis.